Meninjau Ulang Eksistensi Mukjizat Kesembuhan Di Masa Pandemik Covid-19 Perspektif Teologi Pentakosta-Kharismatik - Yosep Belay; Ferry Simanjuntak; Yanto Paulus Hermanto (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2021)
The condition of the Covid-19 pandemic that has never subsided, raises various questions for Pentecostal-Charismatics regarding the concept of God's power and specifically regarding the existence of miraculous gifts of healing. In the context of Christianity, the view of the existence of miracles of healing is divided into two views which are pro and contra. This paper departs from the controversial side especially during this pandemic situation and seeks to present a comprehensive Pentecostal-Charismatic theological perspective. The methodological approach used is descriptive qualitative. The literature study approach is used to analyze the variety of literature related to miracles of healing, as well as brief hermeneutic studies on relevant biblical texts. The results of this study indicate the difference in conceptual framework between Pentecostal-Charismatic theology regarding miracles of healing, where the difference is not only centered on the conceptual side but also backwards on the study of hermeneutics resulting in different responses in practical theological praxis in the life of the congregation today.AbstrakKondisi pandemic covid-19 yang tak kunjung mereda, menghantarkan beragam pertanyaan bagi kalangan Pentakosta-Kharismatik perihal konsep kuasa Allah dan secara khusus mengenai eksistensi karunia mukjizat kesembuhan. Dalam konteks kekristenan, padangan mengenai eksistensi mukjizat kesembuhan terbagi dalam dua pandangan yang pro dan kontra. Tulisan ini bertolak dari sisi kontroversial terutama ditengah situasi pandemic ini serta berusaha untuk menyajikan kerangka pandangan teologi Pentakosta-Kharismatik yang komprehensif. Pendekatan metodologi yang digunakna adalah kualitiatif deskriptif. Pendekatan studi kepustakaan digunakan untuk menganalisa ragam literatur yang berkaitan dengan mukjizat kesembuhan, serta kajian hermeneutik singkat pada teks-teks Alkitab yang relevan. Hasil dari penelitian ini menunjukkan perbedaan kerangka konseptual antara teologi Pentakosta-Kharismatik mengenai mukjizat kesembuhan, dimana perbedaan tersebut bukan hanya berpusat pada sisi konseptualnya namun juga mundur ke belakang pada kajian hermeneutikanya sehingga menghasilkan respons yang berbeda dalam praksis teologi praktika dalam kehidupan jemaat saat ini.